Socioeconomic characteristic of street food vending enterprises in the Vhembe district, Limpopo province - Mahopo, TC; Nesamvuni, CN; Nesamvuni, AE; de Bruyn, Melanie; Van Niekerk, J (Technium Social Sciences Journal, 2022)
The street food business is a crucial indirect driver of the economies of developing countries. It ought not to be ignored as most unemployed people turn to it as their primary means of earning a living to improve their lives. We studied the socioeconomic characteristics of the street food enterprises in the Vhembe district, South Africa. A cross-sectional survey of 511 street vendors (18-75 years old) was conducted. The socioeconomic characteristics of vendors in three towns of the Vhembe district were quantified. Data collected included age, gender, educational level, economic profile, factors influencing entry, foods sold, regulatory issues, and input suppliers. The results highlight the dominance (63.1%) of single middle-aged women (35-44 years old) with high school education and few young adults’ participation (4.1%) in the street food enterprise. About 14% of participants migrated from Zimbabwe to seek employment. Many of them (11.4%) reside in Musina. Lack of opportunities (65%) and financial freedom (90.8%) was the primary motivation for entry into the enterprise. Street food enterprises contributed about 82% of the average household income R6 042.66 made from the enterprise per month. About 50% of the street vendors are affiliated with a local organization. The most commonly cooked foods sold were pap (97.1%) served with chicken (88.8%) or beef (68.3%), with others serving with different vegetables (75.3%). The study recommends the prioritization of the establishment of local representative organizations in collaboration with the authorities to serve as gatekeepers for the sector, such as health checks, enforcing enterprise certification, promoting association for lobbying power and internally settling disputes.